Frequency of Gastric Varices in Cirrhotic Patients with Portal Hypertension Based on Endoscopic Findings - Shakeel, Shaheer; Khan, Muhammad Arif; Khan, Muhammad Mudasser; Khan, Mohammad Usama (Indus Journal of Bioscience Research, 2025)
Background: Portal hypertension tends to complicate liver cirrhosis leading to development of varices. Although gastric varices are not very common as compared to esophageal varices, they are associated with severe bleeding and higher mortality. Purpose: The purpose of the endoscopic study was to determine the incidence of stomach varices in patients with portal hypertension who have cirrhosis. Procedures: This descriptive cross-sectional study was conducted by the Department of Medicine, Bolan Medical College/Hospital in Quetta from 15th January 2025 to 14th April 2025. Non-probability consecutive sampling was used to sample 120 cirrhosis patients who had portal hypertension between the ages of 18 and 60. Major comorbidities, patients who had undergone shunt operations, and those who had undergone variceal treatment were not included. A skilled consultant adopted upper gastrointestinal endoscopy to identify gastric varices. The data was analyzed using SPSS version 25.0. In an attempt to assess the effect modifiers, stratification was done and the frequency and percentages were calculated. The chi-square test was applied and p-value of less than 0.05 considered to be statistically significant. Results: 60.0% of the respondents were males and the mean age among them was 45.2 ± 10.6 years. There were twenty-four (20.0%) with gastric varices. Gastric varices and Child-Pugh class were found to be quite correlated (p = 0.03), and the rate increased with the Class A (10.0%), then Class C (32.5%). There was no significant correlation between age, gender, BMI, period of having cirrhosis, and residence (p > 0.05). Conclusion: Finally, gastric varices elongate very often in patients with cirrhosis, and they are closely associated with the development of advanced liver disease. Routine endoscopic screening is recommended in order to detect and treat the disease at an early stage.